(untitled) (Scientific journal of the Fergana State University, 2023)
This article provides information about the current state of teaching methods in comprehensive schools, the role of chemistry and the chemical industry in human everyday life, as well as the results of scientific research, the purpose of which is to increase students’ interest in learning the basics of chemistry.